Accidental Modopar(©) Poisoning in a Two-Year-Old Child: A Case Report - Lahlou, Adnane (J Crit Care Med (Targu Mures), 2019)
Levodopa is a dopamine precursor and a mainstay treatment in the management of Parkinson’s disease. Its side effects induce dyskinesia, nausea, vomiting, and orthostatic hypotension. Acute levodopa acute poisoning is uncommon, with only a few reported cases in the medical literature. Treatment of poisoning by levodopa is mainly supportive. The case of a child admitted to a hospital for acute levodopa poisoning is presented in this report.